First experiences with intraoperative CT in navigated sacroiliac (SI) instrumentation: An analysis of 25 cases and comparison with conventional intraoperative 2D and 3D imaging. Issue 10 (October 2021) - Privalov, Maxim; Beisemann, Nils; Swartman, Benedict; Vetter, Sven Y.; Grützner, Paul A.; Franke, Jochen; Keil, Holger
Highlights: The intraoperative mobile CT provides excellent image quality that allows reliable assessment of fracture reduction and implant placement even in complex anatomical regions such as the pelvis. The ability to correct complications intraoperatively eliminates the need for revision surgery, improving clinical outcomes and the quality of patient treatment over time. The radiation exposure for medical staff, and potentially also for the patient, can be significantly reduced without prolonging the duration of the surgical procedure. Abstract: Background: Intraoperative imaging is regularly used for intraoperative reduction control and evaluation of the implant position in trauma surgery. 2D imaging is limited, especially in complex anatomical regions such as the pelvis. The introduction of mobile 3D C-arms (CBCT: cone-beam computed tomography) has significantly improved intraoperative assessment. Nevertheless, there are still limitations regarding the field of view and metal artifacts. The purpose of this study was to evaluate the potential of intraoperative computed tomography (iCT) in surgical treatment of sacroiliac (SI) injuries. Methods: Twenty-five cases with injuries of the posterior pelvic ring involving the SI region that were surgically treated with navigated SI screws using the mobile iCT Airo (Brainlab, Munich, Germany) were analysed. Subsequently, the data were compared with historical control groups (CBCT with and without navigation; 2D fluoroscopy only). Results: The average score for subjective image quality achieved using the Likert scale is significantly higher for the iCT (4.48 ± 0.65) than for the CBCT (3.04 ± 0.69) with p = 0.00. The average duration of surgery using iCT was 189.32 ± 88.64 min, which was not significantly different from the control groups ( p = 0.14 - 0.70). The average fluoroscopy time using iCT was 81.96 ± 97.34 s, which was significantly shorter than in all of the control groups ( p = 0.00 - 0.03). The rate for postoperatively detected complications after using iCT was 0% ( n = 0). Compared with the 2D-only control group (25%; n = 1), there is a significant difference ( p = 0.01). The remaining two control groups showed no significant differences ( p = 0.09 - 0.19). Conclusions: The iCT provides excellent image quality that allows reliable assessment of fracture reduction and implant placement even in complex anatomical regions. The radiation exposure for the medical staff is reduced by decreasing the fluoroscopy time without significantly prolonging the surgical time. Overall, the possibility of intraoperative correction improves clinical outcome and patient treatment in the long term.